Resistance to Temephos in populations of Aedes aegypti (Diptera: Culicidae) from western Venezuela - ÁLVAREZ, LESLIE; BRICEÑO, ARELIS; OVIEDO, MILAGROS (Revista Colombiana de Entomología, 2006)
Organophosphate insecticides have played a very important role in the control of Aedes aegypti, vector of dengue fever and dengue haemorrhagic fever in Venezuela and other American countries. For more than 20 years in Venezuela, Temephos has been used as a larvicide and Malathion as an adultcide in control campaigns for this vector. For these reasons we selected five strains of A. aegypti from four Venezuelan states: Trujillo (PTO and SM), Zulia (Z), Falcón (F) and Táchira (TB), to determine levels of resistance to Temephos. Bioassays were conducted with stage IV larvae testing five insecticide concentrations, according to the WHO methodology. After determining the range of resistance, strains TB, Z, F and SM were susceptible with FR50 values below 5. The strain PTO is resistant (6,3 fold). The results suggest that these populations should be under continual surveillance to observe any change in level of resistance to Temephos. Additionally, it is necessary to know the response of any A. aegypti population to be controlled with this insecticide in Venezuela, and that way guarantee its efficacy.